2014
DOI: 10.1159/000358493
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibilities and Clinical Characterization of <b><i>Pseudomonas aeruginosa</i></b> Isolates from Urinary Tract Infections

Abstract: Introduction:Pseudomonas aeruginosa is a uropathogen that is mainly involved in nosocomial infection. The aim of this study was to analyze the antimicrobial susceptibilities and clinical characterization of P. aeruginosa isolates from urinary tract infections (UTIs). Materials and Methods: The study collected all P. aeruginosa UTI strains from a hospital in Chongqing, China, from January 1st, 2010 to December 31st, 2011. The antibiotic susceptibilities of the P. aeruginosa isolates were analyzed using the agar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
1
9
1
Order By: Relevance
“…A high P. aeruginosa susceptibility rate to amikacin (100%), ceftazidime, cefepime, gentamycin, piperacillin/tazobactam (92%), and imipenem (85%) was reported in the current study which was higher than the frequency reported by Zhang et al 24 Genotyping of 18 E. coli strains causing nosocomial infections depicted the presence of three clusters with more than 70% genetic similarity, 12 of 18 strains were isolated from urology or surgical units. These results suggested the possibility of dissemination of these clones, especially in these two units.…”
Section: Discussioncontrasting
confidence: 77%
“…A high P. aeruginosa susceptibility rate to amikacin (100%), ceftazidime, cefepime, gentamycin, piperacillin/tazobactam (92%), and imipenem (85%) was reported in the current study which was higher than the frequency reported by Zhang et al 24 Genotyping of 18 E. coli strains causing nosocomial infections depicted the presence of three clusters with more than 70% genetic similarity, 12 of 18 strains were isolated from urology or surgical units. These results suggested the possibility of dissemination of these clones, especially in these two units.…”
Section: Discussioncontrasting
confidence: 77%
“…is due to the high rate of infection stones, which was similar in the study of Ng et al [11]. The more difficult to treat bacteria such as Pseudomonas aeruginosa or even rarities such as Salmonella typhi may cause treatment failure in primary calculated antibiotic therapy of OPN [14,15]. We agree with van Nieuwkoop et al [16] that imaging is necessary in patients with febrile UTI in the presence of a history of urolithiasis and/or a urine pH ≄7.0 and/or renal insufficiency (estimated glomerular filtration rate ≀40 ml/min/1.73 m 3 ).…”
Section: Discussionmentioning
confidence: 68%
“…6 Any type of surgery (minor to major) or invasive procedure (e.g., endoscopy, percutaneous intervention) in the past 6 months. 7 At least two doses of any antibiotic in the past 3 months preceding HAUTI. 8 Patients with urinary catheter on the day the culture was taken or the day before, including patients with chronic catheters.…”
Section: Resultsmentioning
confidence: 99%